Bangladesh Food System Profile. Better understanding food systems at country level - Hernández, Ricardo; Béné, Christophe; Lundy, Mark M.; Chege, Christine Gacheri Kiria; Wiegel, Jennifer Rebecca; Achicanoy Estrella, Harold Armando (2022)
This Bangladesh food system profile is composed of three main blocks of information: (a) system drivers; (b) system components; and (c) system outcomes. The first main block recognizes how environmental, demographic, technological, political, economic, social, and cultural drivers influence the food system—from production to consumption. The second block considers three components of the system: its actors and activities, the food environment, and consumer behavior. The third block, which is the last, corresponds to the system's outcomes in terms of the nutritional and health status of the population, food security, and the country's environmental and socioeconomic conditions. This profile also presents a comparison of Bangladesh's data against three groups: the country's geographic neighbors (Bhutan, India, Myanmar, and Nepal), countries with similar GDP per capita (Angola, India, Kenya, and Nicaragua), and the world average.